2022
DOI: 10.1063/5.0076865
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electroresistance endurance of capped Hf0.5Zr0.5O2 ultrathin epitaxial tunnel barriers

Abstract: Electroresistance in ultrathin Hf0.5Zr0.5O2 (HZO) films is pivotal toward the implementation of hafnia-based ferroelectrics in electronics. Here, we show that the electroresistance yield and endurance of large capacitors (∼314 µm2) of epitaxial HZO films only 2.2 nm thick grown on SrTiO3 or GdScO3 can be improved using 1 nm SrTiO3 capping layers. It is argued that the main role of the capping layer is to minimize charge transport along grain boundaries, and, thus, a similar strategy can be explored in polycrys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…As LSMO volume is preserved [24], it can be concluded that orthorhombic phase amount increases with the LSMO in-plane lattice parameter at the expenses of the monoclinic one, indicating that epitaxial tensile stress critically favors the formation of the ferroelectric phase. Note that XPS characterization of Hf 0.5 Zr 0.5 O 2 films grown on (001) SrTiO 3 and DyScO 3 , does not reveal significant differences of the Hf oxidation state [28] indicating that the potential effect of the different substrates on the amount of oxygen vacancies is under the detection limit [29]. Atomic force microscopy topographic images (Supplementary materials S3) indicate flat surfaces with root-mean square roughness values below 0.5 nm for all samples, irrespectively of the phases ratio.…”
Section: Resultsmentioning
confidence: 91%
“…As LSMO volume is preserved [24], it can be concluded that orthorhombic phase amount increases with the LSMO in-plane lattice parameter at the expenses of the monoclinic one, indicating that epitaxial tensile stress critically favors the formation of the ferroelectric phase. Note that XPS characterization of Hf 0.5 Zr 0.5 O 2 films grown on (001) SrTiO 3 and DyScO 3 , does not reveal significant differences of the Hf oxidation state [28] indicating that the potential effect of the different substrates on the amount of oxygen vacancies is under the detection limit [29]. Atomic force microscopy topographic images (Supplementary materials S3) indicate flat surfaces with root-mean square roughness values below 0.5 nm for all samples, irrespectively of the phases ratio.…”
Section: Resultsmentioning
confidence: 91%
“…X‐ray photoelectron spectroscopy confirms that Zr has been successfully doped into the HfO 2 (Figure 1c). [ 30,31 ] Inductively coupled plasma atomic emission spectroscopy and energy‐dispersive X‐ray spectroscopy results further verify the proportional and uniform distribution of Hf and Zr in the SNWs (Figure S3, Table S1, Supporting Information). As evidenced by high‐resolution TEM (HRTEM), the single ultrathin nanowire has flexible bent geometries and a soft gel‐like texture (Figure 1b).…”
Section: Resultsmentioning
confidence: 55%
“…However, in the case of ultrathin films, as required for advanced applications, it remains to be elucidated if, after the formation of conductive channels, ferroelectricity is preserved and tunnel electroresistance resulting from ferroelectric polarization switching still persists. Ferroelectric tunnel junctions of epitaxial films have revealed clear signatures of their ferroelectric character down to 2 nm. , On the other hand, epitaxial films allow the fine control of their microstructure, allowing one to tune the relative weight of ferroelectric and ionic contributions to ER. , It has also been demonstrated that conducting channels can be blocked by the deposition of appropriate capping layers. , Therefore, epitaxial ferroelectric HfO 2 films offer a unique opportunity to assess the ferroelectric character of films after conducting filament formation (soft breakdown) and to elucidate if ferroelectric polarization switching still leads to an ER, as in the pristine state.…”
Section: Introductionmentioning
confidence: 99%
“…10,13 It has also been demonstrated that conducting channels can be blocked by the deposition of appropriate capping layers. 15,31 Therefore, epitaxial ferroelectric HfO 2 films offer a unique opportunity to assess the ferroelectric character of films after conducting filament formation (soft breakdown) and to elucidate if ferroelectric polarization switching still leads to an ER, as in the pristine state.…”
Section: ■ Introductionmentioning
confidence: 99%